"To Twist or Not to Twist": Figure‐of‐Eight and Planar Structures of Octaphyrins. Issue 1 (28th November 2016) - Shivran, Neelam; Gadekar, Santosh C.; Anand, Venkataramanarao G.
Abstract: Amongst the various porphyrinoids, octaphyrin has attracted significant attention owing to its diverse syntheses, conformations, and metal‐ligation properties. Octaphyrin is a higher homologue of porphyrin and is formed by linking together heterocycles such as pyrrole, furan, thiophene, and selenophene through α‐α or α‐ meso carbon bonds. The planar conformation is mainly achieved through inversion of the heterocyclic units from the center of macrocycle; avoiding meso ‐bridges; introducing a para ‐quinodimethane bridge; employing a neo‐confusion approach; protonation; and by generating dianionic species. In this Focus Review, recent synthetic advancements in the field of octaphyrins are summarized. The twisted conformation of the octaphyrin binds to two metal ions in a tetracoordinate geometry. The diphosphorus complex of octaphyrin represents the first example of a stable expanded isophlorin. Abstract : Twist and shout : Heterocyclic ring inversion and a figure‐of‐eight configuration are mutually exclusive in expanded porphyrinoids. For octaphyrins in particular, it has been observed that heterocyclic ring inversion is crucial for a macrocycle to maintain a planar conformation.